Mushblok Organic Fertilizer - Razali, Norfazillah; Hamid, Nur’ Amira; Mohamad Faris, Nurul Izzah; Madrom, Mohamad Nadzmi; Wan Mohd Zain, Wan Zuraida (Multidisciplinary Applied Research and Innovation, 2021)
Mushroom block waste is increasing nowadays. It will cause the pollution and also increase the waste production. Due to this problem, this research is producing the MushBlok organic fertilizer (Mushroom block organic fertilizer). It is an organic fertilizer that made from mushroom block waste. This organic fertilizer was made up by using mushroom block composed (Expired) for 5kg, water was 5L, any domestic waste (fruits, vegetable, fish, eggs) for 1kg (optional), yeast-22g, beneficial microorganism (BMO) 2Lto 3L and molasses 0.5L.  The ingredients were mixed together and left for 5 days in a room temperature. The results showed that the organic mushblock increase the growth and also increase the yields of vegetables. Thus, the production of Mushblock is very useful and efficiently prevents the increase of water and pollution. At the same time, this product can generate the profit.